IMPLEMENTASI TEKNIK BERTANYA SEJARAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MAN SENGKOL - Fathurrahman Fathurrahman; Muhammad Nur (CV. ADIBA AISHA AMIRA, 2022)
ABSTRACT This research is motivated by the condition of learning history that has been carried out so far is still very conventional with a style of learning; namely: (1) learning is still teacher centered, does not involve students, (2) the limited knowledge of history teachers in developing student-centered learning approaches and models. This study uses classroom action research, with the aim of improving student learning outcomes and teacher performance. The results of this study include; (1) The application of this questioning technique changes the process and learning outcomes, the initial conditions for learning at MAN Sengkol Pujut so far still use Teacher-centered and students are not yet as learning subjects. The results of learning history are decreasing and students' interest in learning history is low. (2) the questioning technique carried out by partner teachers, namely in the application of the types of questions made through good planning, so that the number and types of questions asked by partner teachers, from low-level and high-level questions are balanced and carried out continuously, (3) partner teachers can carry out learning with good questioning techniques, (4) able to improve student learning outcomes. This can be seen by increasing the average value of students after using the questioning technique. Thus the questioning technique can be used as an alternative in learning history to improve student learning outcomes both in the process and in the form of results or scores.